Peran Pajak Dalam Peningkatan Dunia Pendidikan - Kadarukmi, M.E. Retno (Jurnal Administrasi Bisnis, 2011)
Education has an important role in improving human resources in Indonesia. Edu-cation also affect the full economic growth. Countries that have a population withhigh educational level will have this level of rapid economic growth. Indonesia, inthis case the government has an obligation to fund the development including thedevelopment of education. One of the sources of funds for development financing isfrom tax. Therefore, the government must act wisely in the use of funds has beenobtained from collecting taxes to finance education, so that the move visible roleeducation tax.Keywords: Education, tax, human resources